Psychiatric disorders related to alcohol use (Research, Society and Development, 2022)
Alcoholism is a pathological condition that develops through excessive use of alcohol. It presents as consequences, public health problems, in addition to damage observed in the individual's social networks. In this conception, the study's primary objective is to analyze the use of alcohol and its direct effects on the health and interpersonal relationships of users. In addition, the damage that excessive use of alcohol can bring to the psychological of the dependent will also be discussed, especially in cases in which the emergence of psychiatric diseases has been detected. This is a systematic literature review, which included studies in Portuguese and published between 2017 and 2022. To obtain this answer, this work was based on searches of scientific articles in the indexed databases of the data portal of scientific articles withdrawn from research sources such as: Google Scholar, Scielo, LILACS and PubMed. In its mechanism of action, alcohol, which is a psychotropic substance that depressants the central nervous system (CNS), promotes simultaneous alteration of numerous neuronal pathways, generating a profound neurological impact and translating into several biological and behavioral changes. The multifocal action of alcohol on the CNS results in a general effect of psychomotor depression, difficulties in storing information and logical reasoning, motor incoordination, in addition to stimulation of the reward system, which may explain the development of chemical dependence, it was evident the alcohol can produce symptoms of depression, anxiety, agitation, symptoms that end up harming the physical, psychological and social aspect of the patient.